The prevalence of functional disability and associated factors among older adults living in Bahir Dar City, Northwest, Ethiopia: a community-based cross-sectional study - Yihenew, Addisu; Ejigu Anteneh, Yeshambel; Miheret, Tewodros; Gobezie, Melese; Eriku, Getachew Azeze; Yimer Shibabaw, Yadelew; Kassa, Tesfa (Frontiers in Public Health, 2024)
Background: The limitation of carry out everyday activities independently is a common experience for older adults with functional disabilities, which can hurt their overall well-being.Unfortunately, there is still a dearth of evidence about how common it is among older adults, especially in low-and middle-income countries like Ethiopia. Therefore, the study aimed to assess the prevalence and associated factors of functional disability among older adults living in Bahir Dar city, northwest, Ethiopia, 2023.Method: A community-based cross-sectional study was conducted among older adults (≥60years) living in Bahir Dar city, Northwest, Ethiopia. A total of 598 study participants were included using a multistage sampling technique. Data were collected through intervieweradministered questionnaires. Barthel Index (BI) was used to assess the functional capacity of older adults which comprises ten items. The total score ranges from 0-100. Variables significant in bivariable analysis were entered into multivariable logistic regression analysis. A P<0.05 was considered statistically significant in the final logistic regression model.Results: Among the 598 participants studied, the overall prevalence of functional disability was 29.6 (95% CI: 26.0-33.4). Older age (≥70 years) adjusted odds ratio(AOR): 2.24; 95%